Martin Heidegger Dan Pendidikan Islam Dalam Perspektif Eksistensialisme - Rochim, Ahmad Abdul; Usman, Usman; Sibawaihi, Sibawaihi (J-CEKI : Jurnal Cendekia Ilmiah, 2025)
This article seeks to examine Martin Heidegger’s existentialist philosophy and his perspective on how Islamic educational methods can strengthen students’ morals and religious sense. The design of the literature study used a qualitative approach, which included the evaluation, collection, and examination of relevant materials. According to the findings of the study. Martin Heidegger’s existentialist philosophy offers guidance for educators and learners, for students, education is a means to discover and become a more authentic version of themselves. In this sense, educators should give autonomy to students and support them to become their true selves. Teachers should not limit their teaching methods and goals to memorization; instead, they should incorporate a process of self-discovery for each student.